A randomized, double‐blind trial of triheptanoin for drug‐resistant epilepsy in glucose transporter 1 deficiency syndrome. Issue 7 (21st May 2022) - Striano, Pasquale; Auvin, Stéphane; Collins, Abigail; Horvath, Rita; Scheffer, Ingrid E.; Tzadok, Michal; Miller, Ian; Kay Koenig, Mary; Lacy, Adrian; Davis, Ronald; Garcia‐Cazorla, Angela; Saneto, Russell P.; et al.
Abstract: Objective: This study was undertaken to evaluate efficacy and long‐term safety of triheptanoin in patients >1 year old, not on a ketogenic diet, with drug‐resistant seizures associated with glucose transporter 1 deficiency syndrome (Glut1DS). Methods: UX007G‐CL201 was a randomized, double‐blind, placebo‐controlled trial. Following a 6‐week baseline period, eligible patients were randomized 3:1 to triheptanoin or placebo. Dosing was titrated to 35% of total daily calories over 2 weeks. After an 8‐week placebo‐controlled period, all patients received open‐label triheptanoin through Week 52. Results: The study included 36 patients (15 children, 13 adolescents, eight adults). A median 12.6% reduction in overall seizure frequency was observed in the triheptanoin arm relative to baseline, and a 13.5% difference was observed relative to placebo ( p  = .58). In patients with absence seizures only ( n  = 9), a median 62.2% reduction in seizure frequency was observed in the triheptanoin arm relative to baseline. Only one patient with absence seizures only was present in the control group, preventing comparison. No statistically significant differences in seizure frequency were observed. Common treatment‐emergent adverse events included diarrhea, vomiting, abdominal pain, and nausea, mostly mild or moderate in severity. No serious adverse events were considered to be treatment related. One patient discontinued due to status epilepticus. Significance: Triheptanoin did not significantly reduce seizure frequency in patients with Glut1DS not on the ketogenic diet. Treatment was associated with mild to moderate gastrointestinal treatment‐related events; most resolved following dose reduction or interruption and/or medication for treatment. Triheptanoin was not associated with any long‐term safety concerns when administered at dose levels up to 35% of total daily caloric intake for up to 1 year.